Online masjid community - Mat Ali, Abu Aiman; Yahya, Muhammad Zulhelmi; Ahmad Yazid, Mohamad Azraie; Mat Suri, Mohd Izzat; Ahmad Dahlan, Abdul Rahman (Eclat Research Publication, 2016)
Online Masjid Community is an online platform made to make communication between surrounding Muslim community, access to info related to mosque activities and management mosque easier than before and reachable by community through latest technology. At the same time, this platform can help mosque generate revenue rather than collecting donation from community through online transaction, advertising and booking fees. To develop the Online Masjid community conceptual solution, the Business Model Canvas (BMC) and Value Proposition Design (VPD) Canvas suite of tools were utilized.